ECONOMICS OF SPICES MARKETING IN KWARA STATE, NIGERIA - SALAU, S.A.; OLALERE, I.T.; IBIDOKUN, O. P. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2022)
Spices are regarded as a valuable commodity crop grown for medical and nutritional purposes in Nigeria, its economics and factors influencing marketing margin are scarce in the literature. Specifically, the objectives are to:  describe the organization of ginger and garlic marketing, estimate the costs and returns of ginger and garlic marketing and determine factors affecting ginger and garlic marketing in the study area.  Using the snow-balling approach, 150 respondents were selected from the three major ginger and garlic markets in the Ilorin metropolis of Kwara state. Data collected were analyzed using descriptive statistics, Herfindahl- Hirschman Index (HHI), marketing margin and linear multiple regression. Results indicated that a large proportion of ginger and garlic marketers are male and are of active age. The HHI value revealed that both ginger and garlic markets are competitive and non-concentrated. Furthermore, the marketing margin showed that every ₦1 of sales evolve to a price spread of 0. 49k and 0.40k among the ginger and garlic marketers respectively. The predictors of ginger and garlic marketing are household size, monthly income, years of experience, marketing associations, number of customers and public relation strategies (PR) employed by the respondents. Furthermore, poor credit facilities are the major constraint facing marketers in the study area. The policy aimed at providing both formal and informal credits to marketers should be encouraged. Also, marketers should be trained on the effective use of PR strategies for enhanced marketing margin.   Lastly, it is important to raise awareness about the economic, medical, and nutritional benefits of these spices to enhance marketing.